Chitosan-coated nanoparticles enhanced lung pharmacokinetic profile of voriconazole upon pulmonary delivery in mice. (31st January 2018) - Paul, Paramita; Sengupta, Soma; Mukherjee, Biswajit; Shaw, Tapan K; Gaonkar, Raghuvir H; Debnath, Mita Chatterjee
Aim: Chitosan-coated polylactic- co -glycolic acid nanoparticles of voriconazole (VChNP) were developed to increase residence time and provide sustained drug release locally to treat recurrent lung-fungal infection.Materials & methods: VChNP has been developed using a simple, unique technique and characterized. Pharmacokinetics, lung deposition with time and gamma imaging were conducted with optimized formulations.Results: The deposition of fluorescein isothiocyanate-labeled VChNP in lung was confirmed by confocal microscopy. Gamma-scintigraphic images showed that Tc-99m-labeled VChNP had better pulmonary retention for longer period than that of noncoated formulation. Drastic improvement in pharmacokinetic profile of VChNP than noncoated formulation was observed.Conclusion: Thus, VChNP may be useful for effective pulmonary delivery with improved bioavailability. Such chitosan-coated nanoparticles may open up a new avenue for efficacious treatment of lung-fungal infection. Graphical abstract: